Parasitism with Acanthocephalus ranae in frogs (Pelophylax ridibundus Pallas 1771), from North-east Romania - Iacob O. C. (Helminthologia, 2021)
The present study was carried out on 10 frogs, Pelophylax ridibundus (Pallas, 1771), captured near the river Bahlui, Iasi, between April and May, 2019, for the study of digestive helminths and their effect on the digestive tract. Macroscopic examination of the general cavity revealed distension of the small intestine. The sectioning of the intestinal wall revealed a variable number of parasites (1 – 12) with a whitish cylindrical body, anchored in the duodenal mucosa. The morphological study of the parasites confirmed the species as Acantocephalus ranae. The prevalence of the infection was 60 % and the average intensity was 4.83 ± 4.15. Lesions of the small intestine were characterized by catarrhal enteritis, hemorrhagic spots and ulcers on the mucosa, occlusion and obstruction of the intestinal lumen. Histologically, eosinophilic inflammatory infiltrate in the glandular crypts, mucosal and submucosal edema, fibrosis and conjunctival hyperplasia, total mucosal atrophy, were found. The infection with Acanthocephalus ranae in Pelophylax ridibundus caused severe pathological changes, conditioned by the intensity of the infection, aspects revealed for the first time in Romania.